Sex correction improves the accuracy of clinical dopamine transporter imaging - Honkanen Emma A.; Noponen Tommi; Hirvilammi Risto; Lindholm Kari; Parkkola Riitta; Joutsa Juho; Varrone Andrea; Kaasinen Valtteri (SPRINGER, 2022)
Background
In clinical diagnostic imaging, dopamine transporter (DAT) SPECT scans are commonly evaluated using automated semiquantitative analysis software. Age correction is routinely implemented, but usually no sex correction of DAT binding is performed. Since there are sex differences in presynaptic dopaminergic function, we investigated the effect of DAT sex correction in a sample of healthy volunteers who underwent brain [I-123]-FP-CIT SPECT.
Methods
Forty healthy elderly individuals (21 men and 19 women) underwent brain [I-123]-FP-CIT SPECT, and each subject was examined clinically for motor and non-motor parkinsonian symptoms and signs. Regional specific DAT binding ratios (SBR = [ROI-occ]/occ) were calculated using age correction, and the results were compared to those in normal databases with and without sex correction. The level of regional abnormality was set at 2 standard deviations below the mean values of the reference databases.
Results
In the analysis without sex correction, compared to the mean ratio of the reference database, ten healthy individuals (8 men and 2 women) had abnormally low DAT binding ratios, and four individuals (3 men and 1 woman) had borderline low DAT binding ratios in at least one striatal region. When sex correction was implemented, the ratio of one individual was abnormal, and the ratio of one individual was borderline (both males). There were no clinically significant differences in motor or non-motor symptoms between healthy volunteers with abnormal and normal binding.
Conclusions
A considerable number of elderly healthy male subjects can be interpreted to be dopaminergically abnormal if no sex correction of DAT binding is performed. Sex differences in striatal dopaminergic function should be taken into account when DAT imaging is used to assist clinical diagnostics in patients with suspected neurological disorders.